Metamorphic evolution and Zircon ages of pelitic granulites in eastern Hebei, North China Craton: Insights into the regional Archean P–T–t history - Zhanzhan Duan; Chunjing Wei; Rehman H.U. (My University, 2017)
Archean supracrustal granulites occur as localized slivers or rafts in granitoids, and this particular occurrence of supracrustal granulites has not been much concerned from the perspective of metamorphic evolution. The pelitic granulites in eastern Hebei occur as slivers in TTG gneisses and charnockite. Three pelitic granulite samples involving orthopyroxene–garnet gneiss (JD1334), biotite–garnet gneiss (JD1453) and sillimanite–garnet gneiss (JD15126) were collected from Taipingzhai and Laolijia areas. Based on textural observations and mineral compositions, four generations of assemblages involving final, peak, inclusion and overprinting stages are identified. The observed final assemblage yield P–T conditions of 8.0–9.5 kbar/870–890 °C. The observed peak assemblage characteristic of the absence of the matrix biotite record condition of T > 950 °C with fixed P = 9 kbar. An isobaric cooling path from peak to final assemblage is constrained by mineral isopleths. The inclusion assemblages characterized by plagioclase inclusions with high XAn contents are predicted to be stable at low pressure and/or high temperature field. They form an anticlockwise P–T path. The overprinting assemblage characteristic of coronary garnet (g2) coexisting with fine-grained mineral aggregates defines P–T condition of 10–12 kbar/830–880 °C. The deposition age of the sedimentary protolith of pelitic granulites was ∼2.5 Ga, coeval with the crystallization age of TTG gneisses. Both of them were later subjected to granulite facies metamorphism at ∼2.48 Ga. The Archean anticlockwise P–T paths suggest a tectonic scenario to explain the particular occurrence of the Archean supracrustal granulites. Firstly, supracrustal sediments experienced thermal event under low pressures attributed to the intrusion of high-temperature TTGs, resulting in dehydrations of hydrous phases. Then, the dried metasediments interlayered with iron-bearing formations potentially denser than the surrounding lithologies tend to drop into the TTG magma ocean, causing the pressure-increase in the metasediments. Thirdly, the dropped metasediments experienced cooling process under lower crust in coupled with the crystallization of the surrounding TTG magma to form the observed final assemblages. Finally, they uplifted as a consequence of the doming processes in Archean terranes.
Keywords: Zircon age; pelitic granulites; Hebei; North China Craton; Archean; Докембрий::Архей; Precambrian::Archean